Investigation of the superconducting energy gap in the compound LuNi2B2C by the method of point contact spectroscopy: two-gap approximation: Experimental Methods and Applications - Bobrov, N.L.; Beloborod`ko, S.I.; Tyutrina, L.V.; Chernobay, V.N.; Yanson, I.K.; Naugle, D.G.; Rathnayaka, K.D.D. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
It is shown that the two-gap approximation is applicable for describing the dV/dI(V) spectra of LuNi2B2C–Ag point contacts in a wide interval of temperatures. The values and the temperature dependences of the large and the small gaps in the ab plane and in the c direction were estimated using the generalized BTK model [A. Plecenik, M. Grajacar, S. Benacka P. Seidel, A. Pfuch, Phys. Rev. B49, 10016 (1994)]] and the equations of [S.I. Beloborodko, Fiz. Nizk. Temp. 29, 868 (2003) [Low Temp. Phys. 29, 650 (2003)]. In the BCS extrapolation the critical temperature of the small gap is 10 K in the ab plane and 14.5 K in the c direction. The absolute values of the gaps are D0ab = 2.16 meV and D0c = 1.94 meV. For the large gaps the critical temperature Tc coincides with the bulk, Tcbulk = 16.8 K, and their absolute values are very close, being about 3 meV in both orientations. In the c direction the contributions to the conductivity from the small and the large gaps remain practically identical up to 10–11 K. In the ab plane the contribution from the small gap is much smaller and decreases rapidly as a temperature rises.